The Role Of Job Satisfaction As A Mediating Influence Of Leadership And Organizational Climate On Employee Performance - Ida Bagus Udayana Putra; Melissa Percilla Sutrisman; I Made Suniastha Amertha (Jurnal Ekonomi Kuantitatif Terapan, 2024)
This study aims to analyze the effect of leadership and organizational Climate on employee performance, with jobsatisfaction as an intervening variable. The object of this research is PT Restu Sandhika. The sample in this studywas determined by the census method using all 87 employees as respondents. The data collection method is asurvey method with a questionnaire. The analysis technique used is the inferential analysis technique with PartialLeast Square (PLS). The results found that leadership does not directly affect employee performance but has asignificant effect on job satisfaction. Meanwhile, organizational Climate has a significant positive effect onemployee performance and job satisfaction. In addition, job satisfaction can mediate the relationship betweenleadership and employee performance but cannot mediate the relationship between organizational Climate andemployee performance.